2013
DOI: 10.1095/biolreprod.112.104422
|View full text |Cite
|
Sign up to set email alerts
|

Viral Transduction of Male Germline Stem Cells Results in Transgene Transmission after Germ Cell Transplantation in Pigs1

Abstract: Genetic modification of germline stem cells (GSCs) is an alternative approach to generate large transgenic animals where transgenic GSCs are transplanted into a recipient testis to generate donor-derived transgenic sperm. The objective of the present study was to explore the application of viral vectors in delivering an enhanced green fluorescent protein (EGFP) transgene into GSCs for production of transgenic gametes through germ cell transplantation. Both adeno-associated virus (AAV)- and lentivirus (LV)-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 46 publications
2
63
0
1
Order By: Relevance
“…For instance, goat transgenic sperm for human growth hormone was derived from male goats that had been transplanted with SSCs previously manipulated in vitro [81] . In a report from the same group, pig embryos, transgenic for a reporter gene (enhanced green fluorescent protein), could be obtained after oocytes were fertilized with transgenic sperm from culture transduced and later transplanted SSCs [82] . Very recently, bovine gonocytes were transduced through a lentivirus vector and the reporter transgene product proved the success of the procedure [83] .…”
Section: Gene Technologies and Sscmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, goat transgenic sperm for human growth hormone was derived from male goats that had been transplanted with SSCs previously manipulated in vitro [81] . In a report from the same group, pig embryos, transgenic for a reporter gene (enhanced green fluorescent protein), could be obtained after oocytes were fertilized with transgenic sperm from culture transduced and later transplanted SSCs [82] . Very recently, bovine gonocytes were transduced through a lentivirus vector and the reporter transgene product proved the success of the procedure [83] .…”
Section: Gene Technologies and Sscmentioning
confidence: 99%
“…SSC transplantation is an important tool for several other biotechnological applications such as gene [75] , rats [78] , goats [81] , pigs [82] …”
Section: Germ Cell Transplantationmentioning
confidence: 99%
“…Pigs edited to disrupt the DAZL gene can serve as a model for studying the restoration of human fertility by germ cell transplantation or for producing genetically modified offspring by transfer of genetically modified germline stem cells, as has been demonstrated in pigs (45), goats (46), and rodents (47,48). Gene-edited alleles of APC also could provide a size-relevant model of colon cancer for preclinical evaluation of therapeutics, surgical intervention, or detection modalities.…”
Section: Gene Editing For Single-step Introgression Of Valuable Allelmentioning
confidence: 99%
“…Previous studies demonstrated that several pluripotent/multipotent germline stem cells have been established and characterized by different research groups using various protocols, and murine and human male GSCs can be cultured for long periods and retain the capacity to differentiate into multiple cell types in the presence of serum or feeder cells in vitro. Recently, porcine, goat and bovine mGSCs were cultured and characterized, and these cells shared similar characteristics of ES cells and GSCs (Kanatsu-Shinohara et al 2008;Goel et al 2009;Kuijk et al 2009;Hua et al 2011;Zeng et al 2013;Zheng et al 2013;Park et al 2014). However, the methods available for isolating SSCs and mGSCs from porcine testicular cells have a low efficiency of cell separating, and it is difficult to establish a stable livestock mGSCs line Zheng et al 2013;Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%